The role of SIRT1 activator in preventing endothelial dysfunction: A systematic review in vitro studies evaluating senescence markers and cellular senescence-associated outcomes - Rahma, Oktivani Adelathifa; Rohman, Mohammad Saifur; Akbar, Naufal Zulfikar; Rohman, Ibrahim Abdur; Nurwidyaningtyas, Wiwit (Universitas Brawijaya, 2026)
Background: Endothelial dysfunction, largely driven by endothelial senescence, is a critical factor in the pathogenesis of cardiovascular diseases. SIRT1, a key regulator of vascular homeostasis, has been identified as a potential target for mitigating endothelial senescence. Activators of SIRT1 have shown promise in delaying cellular senescence by modulating senescence markers and inflammatory pathways. However, a comprehensive evaluation of their effectiveness in in vitro models is required. Methods: This systematic review follows PRISMA 2020 guidelines and SYRCLE’s risk of bias assessment. Studies from four databases (PubMed, ScienceDirect, SpringerLink, and Taylor & Francis) were screened based on eligibility criteria, focusing on in vitro studies using Human Umbilical Vein Endothelial Cells (HUVECs) treated with SIRT1 activators. Key outcomes analyzed included senescence-associated β-galactosidase (SA-β-gal), cyclin-dependent kinase inhibitors (CDKIs: p21, p53, and p16), and senescence-associated secretory phenotype (SASP). Results: A total of 20 studies met the inclusion criteria. SIRT1 activators, including dapagliflozin, rhHAPLN1, ginsenoside Rb1, resveratrol, and others, demonstrated significant reductions in SA-β-gal expression, oxidative stress, and inflammatory cytokines (IL-6, IL-1β, and CCL2). Additionally, SIRT1 activation was associated with downregulation of CDKIs and enhanced nitric oxide (NO) bioavailability, contributing to improved endothelial function. Conclusion: SIRT1 activators exhibit potential in delaying endothelial senescence by suppressing senescence markers and inflammatory mediators, thereby preserving endothelial integrity. Future studies should focus on clinical validation to explore their therapeutic applications in endothelial senescence and cardiovascular disease prevention